Evolução de áreas de manguezais na Ilha do Maranhão com dados de Sensoriamento Remoto de 1985 à 2020 - SANTOS, Vitória Régia Sousa Rocha (2023)
The master's thesis aims to investigate the evolution of mangrove areas in Maranhão Island. Maranhão Island is home to the state capital (São Luís) and three other municipalities, being an important ecosystem context at a local and global level due to its vast natural riches. The Island is located in the largest contiguous area of ​​mangroves in the world and has undergone several changes, both anthropogenic and natural, throughout its history. Since the 1985s, there has been a large rural exodus in response to the arrival of projects industries in the region, resulting in continuous changes in the environment. In this study, we carried out spatial comparisons on the Island between 1985 and 2020, using remote data and software specialized (QGIS, ArcGIS and ENVI). There were applications of processing techniques images, with emphasis on the use of the MMRI vegetation index (modular mangrove recognition index), for a more accurate analysis of mangrove vegetation in Landsat 5 satellite images TM and Landsat 8 OLI, obtained from the website of the research institution United States Geological Survey - USGS. Furthermore, data from the MAPBIOMAS project were vectorized and quantified to better visualization and identification of land coverage and use areas. From these analyses, multitemporal maps of mangrove areas on Maranhão Island were created, facilitating characterization, analysis and percentage calculation of mangrove areas in hectares. The results revealed moments of reduction and increase in mangroves throughout the Island's history. Those data show that the mangrove ecosystem in the region can be influenced by several factors, including human actions resulting from urban expansion in São Luís and even the mangroves' own ability to adapt to changes in the environment. Expected that the results of this research contribute to a better understanding of the transformations spaces on Maranhão Island, providing subsidies for the planning and implementation of actions to recover degraded areas, as well as socio-environmental measures.